Planetary-scale wave structures of the earth’s atmosphere revealed from the COSMIC observations - Anisetty, S.K.A.V. Prasad Rao; Brahmanandam, P.S.; Uma, G.; Babu, A. Narendra; Huang, Ching-Yuang; Kumar, G. Anil; Tulasiram, S.; Wang, Hsiao-Lan; Chu, Yen-Hsyang (My University, 2014)
GPS radio occultation (GPS RO) method, an active satellite-to-satellite remote sensing technique, is capable of producing accurate, all-weather, round the clock, global refractive index, density, pressure, and temperature profiles of the troposphere and stratosphere. This study presents planetary-scale equatorially trapped Kelvin waves in temperature profiles retrieved using COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) satellites during 2006–2009 and their interactions with background atmospheric conditions. It is found that the Kelvin waves are not only associated with wave periods of higher than 10 days (slow Kelvin waves) with higher zonal wave numbers (either 1 or 2), but also possessing downward phase progression, giving evidence that the source regions of them are located at lower altitudes. A thorough verification of outgoing longwave radiation (OLR) reveals that deep convection activity has developed regularly over the Indonesian region, suggesting that the Kelvin waves are driven by the convective activity. The derived Kelvin waves show enhanced (diminished) tendencies during westward (eastward) phase of the quasi-biennial oscillation (QBO) in zonal winds, implying a mutual relation between both of them. The El Niño and Southern Oscillation (ENSO) below 18 km and the QBO features between 18 and 27 km in temperature profiles are observed during May 2006–May 2010 with the help of an adaptive data analysis technique known as Hilbert Huang Transform (HHT). Further, temperature anomalies computed using COSMIC retrieved temperatures are critically evaluated during different phases of ENSO, which has revealed interesting results and are discussed in light of available literature.
Keywords: Radio occultation technique; Kelvin waves; Outgoing long-wave radiation (OLR); Quasi-biennial oscillation (QBO); El Niño and Southern Oscillation (ENSO); COSMIC observations; Planetary-scale wave